Enzyme Linked Immunosorbent Assay Test for Antibody of Classical Swine Fever Virus In Timor-Leste (UJI ENZYME LINKED IMMUNOSORBENT ASSAY TERHADAP ANTIBODI VIRUS CLASSICAL SWINE FEVER DI TIMOR-LESTE) - de Carvalho, Rui Daniel; Suartha, I Nyoman; Dharmawan, Nyoman Sadra; Kardena, I Made (Jurnal Veteriner, 2017)
The objective of this study was to evaluate the implementation of Classical Swine Fever (CSF)vaccination on pigs in Timor-Leste. The study was conducted by analyzing the percentage of CSF antibodyin pigs sera that obtained from pigs in four districts which were located in the hills and coast of Timor-Leste. Evaluation was also carried out by observing the dominant factor that affecting the increase ofantibody titers in the sera. A total of 240 pigs sera were taken before and after vaccination and thenchecked for antibodies against of CSF virus by using PrioCheck CSFV Ab ELISA kits (Prionics Ag). Twohundred and forty serums obtained from non-vaccinated pigs and 240 other serum obtained from the samepigs, after being vaccinated with CSF vaccine. Time interval from the first and the second serum collectionwas at least 14 days post-vaccination. The results showed there was a significant difference (P<0.01) forthe presence of antibody in vaccinated pigs compared with the unvaccinated. A total of 75% serum fromvaccinated pigs was found positive for the antibody containing, while only 16.7% of serum from nonvaccinatedpigs was positive. The odd ratio analysis showed that the most influential factor for theincrease of antibody titer against CSF virus was vaccination status. among the other factors of age, sexand geographical study.
Keywords: ELISA; Classical Swine Fever Virus; Antibody